Perayaan Malam Siwaratridi Tengah Budaya Main Game Online "Mabar" Tantangan Spiritualitas Generasi Muda Era Digital - I Nengah Putra Kariana (Sophia Dharma: Jurnal Filsafat, Agama Hindu, dan Masyarakat, 2026)
Siwaratri Holy Night in Hindu tradition represents a sacred moment for self-reflection, self-control, and spiritual awareness through religious observances such as fasting, silence, and night vigil. However, digital technological advancement has introduced new behavioral patterns among youth, particularly online multiplayer gaming culture, which often distracts from spiritual practices. This community service program aims to enhance youth understanding of the philosophical meaning of Siwaratri while promoting responsible digital technology use without neglecting spiritual values. Methods included religious discussions (dharma tula), digital spiritual literacy education, reflective activities, and youth community mentoring. Results indicate increased spiritual awareness, reduced gadget usage during holy days, and stronger commitment to integrating technology positively with religious life. This initiative highlights the importance of integrating religious values and digital literacy to strengthen youth spirituality in the digital era.